Pulmonary artery denervation improves hemodynamics and cardiac function in pulmonary hypertension secondary to heart failure. (July 2019) - Zhang, Hang; Yu, Wande; Zhang, Juan; Xie, Dujiang; Gu, Yue; Ye, Peng; Chen, Shao-Liang
This study aimed to determine the benefits and correlated mechanisms of pulmonary artery denervation (PADN) for heart failure (HF) pulmonary hypertension (PH). PH secondary to HF is associated with poor clinical outcomes because there is no proper therapy for it. PADN showed improved outcomes for patients with HF-PH. However, the underlying mechanisms remain unknown. Supracoronary aortic banding (SAB) was used to create HF-PH models. Sprague-Dawley rats were randomly assigned to control, SAB, sham, SAB with PADN, and SAB without PADN groups. Surgical (longitudinally damaging vessel nerves) and chemical (10% phenol applied to the surface of nerves) PADN was performed for animals in the SAB with PADN group. Morphological, echocardiographic, hemodynamic, and protein expression changes were measured four weeks thereafter. Adrenergic receptor (AR) expressions of pulmonary arteries from four HF-PH patients and four patients without PH were measured. Ten HF-PH patients who underwent PADN were followed-up for six months. SAB-induced HF-PH was achieved by 50% of animals. Surgical and chemical PADN was associated with significant improvements in pulmonary artery muscularization, hemodynamics, and right ventricular functions. In pulmonary arterial specimens from HF-PH patients, β2-AR and α1A/B-AR, as well as eNOS, were downregulated and α1D-AR was upregulated compared to those from patients without PH. PADN led to a mean increase of 84 m during the 6-min walk distance for HF-PH patients at six-month follow-up. HF-PH was characterized by downregulated β2-AR, α1A-AR, and α1B-AR and by upregulated α1D-AR. PADN is associated with significant improvements in hemodynamics and pulmonary artery remodeling.